Covert cerebrospinal fluid dynamics dysfunction: evolution from conventional to innovative therapies - Xu, Yi; Yin, Hua; Li, Lingge; Wang, Xiaodi; Hou, Qinghua (Frontiers in Neurology, 2025)
Cerebrospinal fluid (CSF) dynamics disorders are intricately linked to diverse neurological pathologies, though they usually are mild and covert. Contemporary insights into glymphatic system function, particularly the CSF transport, drainage, and its role in clearing metabolic waste and toxic substances in both normal and pathological states, and the pivotal role of aquaporin-4 (AQP4) in CSF-interstitial fluid (ISF) exchange, have established novel theoretical frameworks of subclinical CSF dynamics dysfunction, and have promoted the development of non-surgical therapeutic approaches for them simultaneously. This review comprehensively analyzes the advancement of non-surgical interventions for CSF dynamics disorders, emphasizing the transition from established methodologies to innovative approaches. Current non-surgical treatment strategies primarily encompass three directions: pharmacological therapy, physical therapy, and biological regulation therapy. In terms of pharmacological interventions, developments from traditional diuretics to novel small-molecule drugs show promising therapeutic potential. In physical therapy, innovative techniques such as lower body negative pressure, transcranial magnetic stimulation, and vagus nerve stimulation have provided new options for clinical practice. Meanwhile, biological regulation therapy, exemplified by recombinant VEGF-C administration, has established novel therapeutic paradigms. These therapeutic strategies have demonstrated potential in improving CSF dynamics and enhancing CSF waste elimination. Future research should focus on developing individualized treatment protocols, elucidating of therapeutic mechanisms, and assessing longitudinal outcomes. This will facilitate the development of more precise therapeutic strategies and exploration of optimized multimodal treatment combinations in handling the so-called convert CSF dynamics dysfunction.